The Influence of eCommerce Live Streaming on Purchase Intention and Gift-giving Intention Mediated by Swift Guanxi - Verrell Juvenio Dotulong; Juliani Dyah Trisnawati; Veny Megawati; Ryan Gerry Patalo (Jurnal Manajemen dan Kewirausahaan, 2026)
Live streaming ecommerce has recently become very popular among internet users, especially millennials and Gen Z. Shopee and TikTok are frequently accessed ecommerce platforms that have live streaming features. This study aims to examine the effect of live streaming ecommerce on purchase intention and gift-giving intention among users of the Shopee and TikTok platforms. This study used a quantitative method by distributing questionnaires to a sample of 155 respondents. Data analysis was conducted using Partial Least Square (PLS), considering variables such as telepresence, flow, guidance shopping, and metavoicing on purchase intention and gift-giving intention and swift guanxi as a mediator variable. The results of this study indicate that the variables of telepresence, guidance shopping, have a positive effect on swift guanxi. The swift guanxi variable has a positive effect on purchase intention and gift-giving intention. Then telepresence, flow, guidance shopping, and metavoicing have a positive effect on purchase intention and gift-giving intention through swift guanxi.